Entre territórios e terreiros: yorubá, velhos deuses no novo mundo - Emerson Costa de Melo (2014)
Studies on the formation of Candomblé of Yoruba origin, specifically of Ketu nation in Brazil are numerous. However, the approach is still rare for such phenomena in Geographical Science. In this sense, the present study aims from a Geo-Historical analysis, understand the forms of space-territorial organization of Yoruba people in Africa and its impact in the formation of the first Candomblé temple of Ketu origin in Brazil, the Candomblé of Barroquinha or Ìyá Omi Àse Àirá Intilè, on the period corresponding to the last decade of the eighteenth century to the mid nineteenth century. To do so, was established a dialogue with the suggested approach by the Cultural Geography, comprising the culture as a phenomenon inherent to individuals and civilizations, while a producer element of territories and territoriality.Thus, the present work focus on rereading of worldview and territory to the Yoruba as well as the white hegemonic mechanisms that forcibly contributed to his deterritorialization due to the phenomenon of black slavery in the New World, and consequently, its reterritorialization in Brazilian lands, specifically in the formation of the candomblé temple of Barroquinha.It is considered that this process is related to the production of a peculiar Geography constituted of the restoration of the bond of men with their ancestrals in brazilian lands, intimate relationship with the earth, which allowed to such individuals the reterritorialization not only spatially, but socially because inherent in this process is the recovery of their liberty - as a historical subject and articulator of moviments - in face of a slave society.